Traffic Simulation Model for Port Planning and Congestion Prevention - LI, Baoxiang (Institutional Knowledge at Singapore Management University, 2016)
Effective management of land-side transportation provides the competitive advantage to port terminal operators in improving services and efficient use of limited space in an urban port. We present a hybrid simulation model that combines traffic-flow modeling and discrete-event simulation for land-side port planning and evaluation of traffic conditions for a number of what-if scenarios. We design our model based on a real-world case of a bulk cargo port. The problem is interesting due to complexity of heterogeneous closed-looped internal vehicles and external vehicles traveling in spaces with very limited traffic regulation (no traffic lights, no traffic wardens) and the traffic interactions with port operations such as loading and unloading cargos. Our simulation results show interesting decision-support scenarios for decision makers to evaluate future port planning possibilities and to derive regulation policies governing the port traffic.